2019
DOI: 10.1080/00952990.2019.1669628
|View full text |Cite
|
Sign up to set email alerts
|

Considering abuse liability and neurocognitive effects of cannabis and cannabis-derived products when assessing analgesic efficacy: a comprehensive review of randomized-controlled studies

Abstract: Background-Pain is the most frequent indication for which medical cannabis treatment is sought. Objectives-The clinical potential of cannabis and cannabis-derived products (CDPs) relies on their efficacy to treat an indication and potential adverse effects that impact outcomes, including abuse liability and neurocognitive effects. To ascertain the extent to which these effects impact therapeutic utility, studies investigating cannabis and CDPs for pain were reviewed for analgesic efficacy and assessments of ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…The methods here described may serve as model to examine the potential therapeutic and adverse effects of cannabinoids—and other nonopioid analgesics—among persons receiving opioid agonist therapy for OUD. Towards that end, we combined multidimensional outcome measures—including measures of pain sensitivity, abuse potential, opioid withdrawal, cognitive performance and physiological outcomes—in accordance with the growing consensus to standardize the study of analgesics that have addictive potential 74,75 . Both cannabinoid and opioid receptors are G‐protein‐coupled receptors with downstream effects of adenylyl cyclase activity, calcium channel activation and downstream neurotransmitter release 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods here described may serve as model to examine the potential therapeutic and adverse effects of cannabinoids—and other nonopioid analgesics—among persons receiving opioid agonist therapy for OUD. Towards that end, we combined multidimensional outcome measures—including measures of pain sensitivity, abuse potential, opioid withdrawal, cognitive performance and physiological outcomes—in accordance with the growing consensus to standardize the study of analgesics that have addictive potential 74,75 . Both cannabinoid and opioid receptors are G‐protein‐coupled receptors with downstream effects of adenylyl cyclase activity, calcium channel activation and downstream neurotransmitter release 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Towards that end, we combined multidimensional outcome measures-including measures of pain sensitivity, abuse potential, opioid withdrawal, cognitive performance and physiological outcomes-in accordance with the growing consensus to standardize the study of analgesics that have addictive potential. 74,75 Both cannabinoid and opioid receptors are G-protein-coupled receptors with downstream effects of adenylyl cyclase activity, calcium channel activation and downstream neurotransmitter release. 15 Further, these receptors are densely colocalized in brain regions that mediate pain, reward and cognition-such as the periaqueductal gray (PAG), locus coeruleus and higher level cortices.…”
Section: Methodological and Mechanistic Implicationsmentioning
confidence: 99%
“…Chronic pain is often comorbid with depression and anxiety ( Feingold et al, 2019 ). However, a comprehensive review of placebo-controlled studies of cannabis and CBMPs for pain, found that few assessed abuse liability ( Cooper and Abrams, 2019 ). Feingold et al (2017) found the prevalence of problematic medical cannabis use to be relatively high, with 21.2% (DSM-IV) and 10.6% (modified Portnoy’s Criteria (PC)) amongst chronic pain patients.…”
Section: Introductionmentioning
confidence: 99%
“…Together these studies suggest that oral administration routes such as buccal or swallowing is preferred as it could reduce the risk of abuse-related subjective (and neurocognitive) effects ( Cooper and Abrams, 2019 ). However, potential misuse and problematic use of oral cannabinoids have been found in a prospective observational study of 265 patients initiating oral cannabinoid therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Amid this backdrop of increasing legalization and use of cannabis, as well as growing evidence base regarding the potential risks and benefits of cannabis (Friedman et al, 2019; Nugent et al, 2017; Ware et al, 2015; Honarmand et al, 2011; Semple et al, 2005; Cooper & Abrams, 2019), nursing and medical boards across the United States are starting to expect health care professionals (HCPs) to receive education on this topic (FSMB, n.d.). The National Council of States Board of Nursing provide best practice data for APRNs certifying qualifying conditions in patients seeking cannabis for medical purposes (NCSBN Medical Marijuana Guidelines Committee, 2018).…”
Section: Introductionmentioning
confidence: 99%